ANALISA JANGKA WAKTU PENGIRIMAN PADA LOGISTIK TRANSPORTASI PT.XYZ DENGAN METODE VALUE STREAM MAPPING - Caecilia Dewi; Dadang Surjasa; Parwadi Moengin (JURNAL TEKNIK INDUSTRI, 2012)
As petroleum construction company with working area spread in the whole world, PT. XYZ is required to always innovate both in terms of technology and in terms of management of management. XYZ Company considers that the period of time in the movement of materials, inventory and assets as well as cost control is the key of price and quality provided to consumers. This thesis try to give suggestions for improvement are made based on analysis of the current situation and seek a reduction in the delivery period through transportation andlogistics operational needs of the company. Study using stage 1). Mapping the condition of the delivery process by utilizing the concept of value stream mapping. 2). Identification of waste (waste) 3). Analyze waste using 5 why, 4) root cause analysis. 4). Eliminating nonvalue added time in the shipping process on logistics. 5). Formulate proposed implementation strategy to provide good quality service to consumers.